1993
DOI: 10.2166/wst.1993.0079
|View full text |Cite
|
Sign up to set email alerts
|

Survival of Plant Pathogens and Weed Seeds during Anaerobic Digestion

Abstract: The survival of Plasmodiophora brassicae was studied at digestion temperatures of 35 °C and 55 °C in laboratory batch digesters within one and two weeks, respectively. The study showed that digestion at 55 °C almost completely reduced the ability of infecting bait plants. The seeds of Rumex obtusifolius and Lycopersicon lycopersicum (tomatoes) were completely destroyed at 55 °C and a digestion time of 14 days, in laboratory batch digesters. The experiments carried out in a two sta… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

2
29
1
1

Year Published

1994
1994
2015
2015

Publication Types

Select...
8
2

Relationship

0
10

Authors

Journals

citations
Cited by 46 publications
(33 citation statements)
references
References 0 publications
2
29
1
1
Order By: Relevance
“…Section 3.5 and e.g., [38]). In contrast to findings from laboratory batch trials that strongly reduced germinable weed seeds [67,68], farmers noticed a higher weed pressure, which might be induced by a higher nitrogen availability, resulting in the competition for factors important for crop growth (water, light). Other observed aspects such as a higher risk for erosion and a less perpetual fertilizing effect can be associated with the lower structure and dry matter contents of digestates compared to unfermented slurry, resulting in lower abilities to avoid erosive incidents and a lower proportion of more strongly embedded and therefore long-term available nitrogen.…”
Section: Avoidance Of Land Use Competition Between Food and Energy Thcontrasting
confidence: 90%
“…Section 3.5 and e.g., [38]). In contrast to findings from laboratory batch trials that strongly reduced germinable weed seeds [67,68], farmers noticed a higher weed pressure, which might be induced by a higher nitrogen availability, resulting in the competition for factors important for crop growth (water, light). Other observed aspects such as a higher risk for erosion and a less perpetual fertilizing effect can be associated with the lower structure and dry matter contents of digestates compared to unfermented slurry, resulting in lower abilities to avoid erosive incidents and a lower proportion of more strongly embedded and therefore long-term available nitrogen.…”
Section: Avoidance Of Land Use Competition Between Food and Energy Thcontrasting
confidence: 90%
“…These latter authors also found that AD reduced swine manure total and volatile solid concentrations by up to 80% resulting in improved manure homogeneity and lowered viscosity allowing more uniform land application [4]. Nevertheless, the higher levels of mineral N found in the slurry, mainly ammonia, may also lead to an increase in the level of phytotoxicity of the slurry, thereby affecting seed germination and plant growth after land-spreading of this co-product into soils [124]. The presence of other phytotoxic substances, such as volatile fatty acids (i.e., acetic, propionic and butyric acids), as well as the high content of soluble salts may contribute to the slurry phytotoxicity [125].…”
Section: Influence Of Anaerobic Digested Slurry On the Soil Microbiotamentioning
confidence: 96%
“…Although scientific findings on seed germinability after anaerobic digestion are inconsistent (Allan et al, 2003), several experiments have shown the high potential of AD for decreasing or destroying seed viability (Engeli et al, 1993;Šarapatka et al, 1993;Westerman et al, 2012aWesterman et al, , 2012b as well as for the extension of germination time (Allan et al, 2003).…”
Section: Germinability Reductionmentioning
confidence: 99%